Mathematics for economics - Hoy, Michael, 1953 September 22-; Livernois, John Richard; McKenna, C. J. (Cambridge, Massachusetts : The MIT Press, 2022)
"A textbook teaching the mathematical concepts and methods necessary for economic research and analysis"--
Revised edition of the authors' Mathematics for economics, c2011.
Includes bibliographical references and index.
Keywords: Economics, Mathematical